2017
DOI: 10.22158/asir.v1n2p90
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Peste des Petits Ruminants (PPR) Disease Propagation and Control Strategies Using Memoryless State Transitions

Abstract: Peste des Petits Ruminants (PPR) is an infectious disease affecting goats and sheep. PPR has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Few studies have been reported in developing mathematical models to simulate and assess the effectiveness of various PPR control strategies. Mitchell et al (2017) [ 6 ] noticed a lack of empirical studies on PPR. Such models provide policy-makers with a tool to develop powerful containment strategies for handling out-breaks of PPR by understanding how it spreads through herds, the uncertainty of the disease parameters, and the impact of each herd’s configuration on the disease’s spread.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been reported in developing mathematical models to simulate and assess the effectiveness of various PPR control strategies. Mitchell et al (2017) [ 6 ] noticed a lack of empirical studies on PPR. Such models provide policy-makers with a tool to develop powerful containment strategies for handling out-breaks of PPR by understanding how it spreads through herds, the uncertainty of the disease parameters, and the impact of each herd’s configuration on the disease’s spread.…”
Section: Introductionmentioning
confidence: 99%
“…The NAADSM (North American Animal Disease Spread Model (54,55), autoregressive integrated moving average model (ARIMA) (56), Least Cost Path (LCP) (57), Random forest (44) Ensemble Algorithm (58), Event-Driven Memoryless model of state transitions. (59), Regression Tree Models (44) and Mantel Correlograms (15), which were employed to investigate the relationship between genetic distances and various measures of network and geographic distance. Moreover, 4 studies formally analyzed PPR seasonality through the assessment of seasonal trends distributed geographically and socioeconomically (31,37,43,60)…”
Section: Resultsmentioning
confidence: 99%
“…GIS-based multi-criterion decision analysis was used to identify areas at risk of PPR occurrence and spread (62). Event-driven model of PPR developed from susceptible-exposed-infectious-recovered (SEIR) model was used to study how the virus propagates in memoryless state transitions in Afghanistan (59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the context, mass or targeted vaccination is required [ 4 , 6 ]. In any case, logistical support like cold chains is crucial for effective PPR vaccination campaigns [ 7 , 8 ]. In addition, socio-economic factors that affect willingness to vaccinate or access to vaccines can jeopardize their success.…”
Section: Introductionmentioning
confidence: 99%